Advancements in the Protocol for Rate of Force Development/Relaxation Scaling Factor Evaluation - Smajla, Darjan; Žitnik, Jure; Šarabon, Nejc (Frontiers in Human Neuroscience, 2021)
Brief submaximal actions are important for wide range of functional movements. Until now, rate of force development and relaxation scaling factor (RFD-SF and RFR-SF) have been used for neuromuscular assessment using 100–120 isometric pulses which requires a high level of attention from the participant and may be influenced by physiological and/or psychological fatigue. All previous studies have been conducted on a smaller number of participants which calls into question the eligibility of some of the outcome measures reported to date. Our aims were: (1) to find the smallest number of rapid isometric force pulses at different force amplitudes is still valid and reliable for RFD-SF slope (kRFD-SF) and RFR-SF slope (kRFR-SF) calculation, (2) to introduce a new outcome measure – theoretical peak of rate of force development/relaxation (TPRFD and TPRFR) and (3) to investigate differences and associations between kRFD-SF and kRFR-SF. A cross-sectional study was conducted on a group of young healthy participants; 40 in the reliability study and 336 in the comparison/association study. We investigated the smallest number of rapid isometric pulses for knee extensors that still provides excellent reliability of the calculated kRFD-SF and kRFR-SF (ICC2,1 ≥ 0.95, CV < 5%). Our results showed excellent reliability of the reduced protocol when 36 pulses (9 for each of the 4 intensity ranges) were used for the calculations of kRFD-SF and kRFR-SF. We confirmed the negligibility of the y-intercepts and confirmed the reliability of the newly introduced TPRFD and TPRFR. Large negative associations were found between kRFD-SF and kRFR-SF (r = 0.502, p < 0.001), while comparison of the absolute values showed a significantly higher kRFD-SF (8.86 ± 1.0 /s) compared to kRFR-SF (8.03 ± 1.3 /s) (p < 0.001). The advantage of the reduced protocol (4 intensities x 9 pulses = 36 pulses) is the shorter assessment time and the reduction of possible influence of fatigue. In addition, the introduction of TPRFD and TPRFR as an outcome measure provides valuable information about the participant`s maximal theoretical RFD/RFR capacity. This can be useful for the assessment of maximal capacity in people with various impairments or pain problems.